Optimalisasi Minat Masyarakat dalam menjalankan ibadah sholat berjama’ah (studi kasus: Masjid Al Muhajirin Desa Padang kuas kecamatan Sukaraja kabupaten Seluma) - Ismail; putri, tiara andika; Mona Lisa Duwi Sari; Andina Syahrani Ginting; Habi Adriansyah; Sendi Balinsu (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This type of research uses qualitative research, namely the data obtained is described in words or sentences systematically, factually, accurately about the phenomena raised in the study, then the data is analyzed to obtain conclusions.The conclusion from the results and discussion above shows that the lack of congregation of Al-Muhajirin Mosque in Jalur Hamlet, Padang Kuas Village is caused by several factors, both internal and external. Internal Factors: The religious knowledge of the community, especially regarding the importance of congregational prayer, is still low. Many do not realize that praying in congregation at the mosque is more advisable than at home. There is a tendency to be lazy among the community, which is caused by a lack of understanding of the importance of congregational prayer and a lack of religious education at home and in the neighborhood. External Factors. The majority of the community work as rubber, palm oil and cattle farmers, which keeps them busy from morning to evening. The long distance from the plantation and fatigue after work make them prefer to pray at home rather than at the mosque. Although the majority of the population is Muslim, the presence of non-Muslims also contributes to the quietness of the mosque as they do not use the mosque for worship. Overall, the lack of worshipers at Al-Muhajirin Mosque is caused by a combination of a lack of religious understanding, laziness, busy work, and religious differences among the community.